Clinical Reasoning: A 23-Year-Old Man With Progressive Asymmetric Weakness and Numbness. (4th April 2023) - Kaplan, Emma H.; Torabian, Kaveh; Edwards, Camille V.; Kaku, Michelle C.; Anand, Pria; Lau, K. H. Vincent
Abstract : We report a case of a 23-year-old man who presented with progressive asymmetric weakness and numbness in his distal extremities over 4 months, with initial symptoms starting days after a coronavirus 2019 (COVID-19) vaccine booster. Initial neurologic examination was notable for distal weakness of both upper and lower extremities that was more pronounced on the left, complete areflexia, and decreased distal sensation to pinprick and vibration without loss of proprioception. Nerve conduction studies demonstrated a generalized, non–length-dependent, sensorimotor, demyelinating polyneuropathy, with conduction block seen in multiple compound muscle action potentials. Sensory nerve action potentials were normal in absolute terms but had asymmetric amplitudes. Based on the patient's nerve conduction studies, he was diagnosed with a specific immune-mediated neuromuscular disorder. He was started on intravenous immunoglobulin, but within days of the first infusions experienced a rare and potentially life-threatening complication. He received appropriate treatment and was started on alternative immunotherapy, after which his symptoms improved. Our case exemplifies the features of a specific subtype of a more common immune-mediated neuromuscular diagnosis with unique elements of history, examination, and nerve conduction studies that required interpretation in the clinical context. We also discuss a rare side effect of a commonly used immunotherapy and its risk factors and comment on the likelihood that this diagnosis may be related to a preceding COVID-19 vaccine booster.